Bureaucracy of Smart City Development in Bandung City - Anzani, Elvira Aprilla (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Smart city is a city management concept based on Information and Communication Technology (ICT) so that the city becomes smarter and more efficient in the utilisation of various existing resources, as well as improving services and the quality of life of urban communities while still promoting environmental sustainability. Bandung is one of the cities in Indonesia that has implemented the Smart City Concept. This research aims to find out how the smart city bureaucracy in Bandung City by looking at aspects of Smart Governance, Smart Environment, Smart Economy, Smart Living, Smart Mobility, Smart Society, and Smart People as the main branding in the implementation of smart cities in the city of Bandung, this research is basically carried out qualitatively where the author collects several documents, files, interviews and literature studies to gain an understanding of the smart city bureaucratic process in Bandung City with the results of the discussion that the smart city that is run still has obstacles in its implementation, these obstacles are based on communication, resources, disposition, and bureaucracy that are not fully ready to run.